2020
DOI: 10.1111/jnc.15211
|View full text |Cite
|
Sign up to set email alerts
|

Bag‐1 mediates glucocorticoid receptor trafficking to mitochondria after corticosterone stimulation: Potential role in regulating affective resilience

Abstract: Molecular abnormalities within the Glucocorticoid Receptor (GR) stress signaling pathway involved in dysfunction of mitochondria and confer vulnerability to stressrelated psychiatric disorders. Bcl-2 associated athanogene (Bag-1) is a target for the actions of mood stabilizers. Bag-1 interacts with GR, thereby regulating glucocorticoid function. In this study, we investigate the potential role of Bag-1 in regulating GR translocation into mitochondria. Corticosterone (CORT) treatment significantly enhanced Bag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The important role of Bag-1 in GR mitochondrial translocation was demonstrated when Bag-1 over-expressing cortical neurons blocked the Cort-induced decrease of mitochondrial GR after long-term treatment with high doses of Cort. Consistent with the in vitro results, chronically Cort-treated Bag-1 over-expressing mice blocked the decrease in mitochondrial GR, reversed the anhedonia-like behavior as well as the depressive-like behavior induced by chronic Cort treatment compared to wild type mice [68]. Taken together, GCs exhibit dose-and time-dependent effects on neuronal mitochondrial function, neuronal viability, GR mitochondrial translocation as well as on the formation of the complexes GR/Bcl-2 and GR/Bag-1 in neurons.…”
Section: Neural Cells and Brain Tissuesupporting
confidence: 86%
See 4 more Smart Citations
“…The important role of Bag-1 in GR mitochondrial translocation was demonstrated when Bag-1 over-expressing cortical neurons blocked the Cort-induced decrease of mitochondrial GR after long-term treatment with high doses of Cort. Consistent with the in vitro results, chronically Cort-treated Bag-1 over-expressing mice blocked the decrease in mitochondrial GR, reversed the anhedonia-like behavior as well as the depressive-like behavior induced by chronic Cort treatment compared to wild type mice [68]. Taken together, GCs exhibit dose-and time-dependent effects on neuronal mitochondrial function, neuronal viability, GR mitochondrial translocation as well as on the formation of the complexes GR/Bcl-2 and GR/Bag-1 in neurons.…”
Section: Neural Cells and Brain Tissuesupporting
confidence: 86%
“…The role of Bag-1 in GR mitochondrial translocation was further investigated by Luo et al who examined Cort dose and time effects on Bag-1/GR complex formation and GR mitochondrial translocation in cortical neuronal cultures and in animal studies [ 68 ]. Their data revealed that short-term treatment with high doses of Cort significantly enhanced the formation of the Bag-1/GR complex and GR mitochondrial translocation, whereas after long-term and high dose incubation of Cort, the Bag-1/GR colocalization and mitochondrial GR were reduced, implicating that Bag-1 mediates the GR mitochondrial trafficking [ 68 ]. The important role of Bag-1 in GR mitochondrial translocation was demonstrated when Bag-1 over-expressing cortical neurons blocked the Cort-induced decrease of mitochondrial GR after long-term treatment with high doses of Cort.…”
Section: Mitochondrial Glucocorticoid Receptor and Apoptosismentioning
confidence: 99%
See 3 more Smart Citations